An Analysis of Community Satisfaction Index on Health Service Quality: CFA and Gap Analysis - Lina Alfiyani; Noor Alis Setiyadi; Asmirati Yakob; Didik Mulyono; Rohmat Rohmat; Mohammad Fathur Rizqi (Universitas Muhammadiyah Surakarta, 2023)
The Community Satisfaction Index is the focus of attention because it is a reference in evaluating health service policies on the quality of hospital services. Service quality is a determinant factor of patient safety to reduce the incidence of mortality in hospitals. Crossectional is the research design used. The study was conducted from April to June 2023, the population is all patients in the hospital in 2023, and Simple random side as a sampling technique of 136 research subjects. The research variables are performance, expectations, and the Community Satisfaction Index which consists of nine elements, namely requirements; systems, mechanisms, and procedures; turnaround time; cost; product specification type of service; competence of the executor; executor behavior; handling of complaints, suggestions, and inputs. Data collection using questionnaires that have previously been tested for confirmatory factor analysis. Test questionnaires and analyze research results with gap analysis using Wilcoxon in the STATA program. The test results of confirmatory factor analysis showed that RMSEA values = 0.04, CFI = 0.99, χ2 / df = 1.05, and TLI = 0.99 showed that the model met goodness-of-fit. The gap analysis shows that in the 9 elements of the Community Satisfaction Index, 2 elements are not different, namely the competence of the implementer (z = -1.570, p = 0.116) and the behavior of the implementer (z = -1.414, p = 0.157). It is hoped that the results of the research can be used as material for the evaluation of hospital policies.